Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3389/fnins.2021.738347
|View full text |Cite
|
Sign up to set email alerts
|

Identification of DNA Methylation Changes That Predict Onset of Post-traumatic Stress Disorder and Depression Following Physical Trauma

Abstract: Post-traumatic stress disorder (PTSD) and major depressive disorder (MDD) are commonly experienced after exposure to highly stressful events, including physical trauma, yet, biological predictors remain elusive. Methylation of DNA may provide key insights, as it likely is reflective of factors that may increase the risk in trauma patients, as DNA methylation is altered by previous stressors. Here, we compared DNA methylation patterns using bisulfite sequencing in patients with a physical trauma that required m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…When comparing individuals diagnosed with PTSD to those non-PTSD control subjects, epigenetic changes abound. Hypomethylation is seen across the Nr3c1 promoter [74,77,80,93], UBE2L3 (Ubiquitin-conjugating enzyme) promoter [92], AHRR (aryl hydrocarbon receptor) [99], F2R, CNPY2, BAIAP2L1, and TBXAS1 [100]. On the contrary, some research efforts have shown the hypermethylation of various gene regions.…”
Section: Traumatic Stressmentioning
confidence: 99%
“…When comparing individuals diagnosed with PTSD to those non-PTSD control subjects, epigenetic changes abound. Hypomethylation is seen across the Nr3c1 promoter [74,77,80,93], UBE2L3 (Ubiquitin-conjugating enzyme) promoter [92], AHRR (aryl hydrocarbon receptor) [99], F2R, CNPY2, BAIAP2L1, and TBXAS1 [100]. On the contrary, some research efforts have shown the hypermethylation of various gene regions.…”
Section: Traumatic Stressmentioning
confidence: 99%
“…However, there was a strong association between clinical anxiety and PTPRN2 (rs3857647), which is required for noradrenaline, dopamine, and serotonin accumulation in the brain. Hypermethylated cytosine sites of PTPRN2 have been linked to depression in trauma survivors ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…Four out of eleven genes associated with methylation biomarkers have been reported as relevant in previous research. [10,[69][70][71][72][73][74][75][76] In previous studies, the altered methylation patterns of the INPP5A gene were associated with cognitive functions in both blood and the hippocampus samples. [69,70] The DIP2C gene has been previously reported to undergo changes in its methylation patterns in studies related to anxiety disorder, post-traumatic stress disorder (PTSD), and major depressive disorder.…”
Section: The Interpretation Of Eleven Genes Associated With 17 Methyl...mentioning
confidence: 90%
“…[69,70] The DIP2C gene has been previously reported to undergo changes in its methylation patterns in studies related to anxiety disorder, post-traumatic stress disorder (PTSD), and major depressive disorder. [10,[71][72][73][74] Furthermore, despite their distinct genomic positions, both INPP5A and DIP2C have been identified as markers in a blood-based study for diagnosing anxiety disorders. [75] The methylation and gene expression patterns of the ATP5F1A gene are known to be associated with Alzheimer's disease.…”
Section: The Interpretation Of Eleven Genes Associated With 17 Methyl...mentioning
confidence: 99%